Dampak Kerjasama Pertahanan Indonesia dan Amerika Serikat terhadap Pencapaian Minimum Essential Force (MEF) Tahap II - Ervin, Andrew Figo Maulana (Global and Policy Journal of International Relations, 2022)
ABSTRACTWith so many unwanted threats waiting to bring peril to anyone in the Asia-Pacific region, Indonesia is required to increase its defense capabilities to an ideal level, in order to be ready to face disputes that may have the potential to pose a threat not only to Indonesia's stability but also to the region or even the world. Therefore, a modernization program that aims to increase Indonesia's defense capability, called the Minimum Essential Force (MEF), was initiated in 2010, followed by predetermined stages that have been agreed upon by the Indonesian government. To complete all MEF stages, Indonesia must carry out various kinds of defense acquisitions, which can be done through bilateral cooperation. The United States, a country that is capable of producing advanced defense equipment, has become a strong partner for Indonesia and has contributed to the MEF program through many defense procurement contracts. During MEF phase II (2015–2019), the two countries reached many defense agreements in terms of military equipment. Therefore, through this research, the author will analyze the contribution of Indonesia-US defense cooperation in MEF phase II, which will lead to the improvement of Indonesia's defense capability.Keywords: Threats, Defense, Cooperation, MEF, ProcurementDOI: https://doi.org/10.33005/jgp.v10i02.3746